THE BEHAVIOR IN UTILIZING INTERNET BANKING AS COMMUNICATION MEDIA - Santoso, Aprih; Kurniawati, Emaya (Sekolah Tinggi Ilmu Ekonomi Semarang, 2018)
The rapid development of information technology is the impact of globalization. The development of information technology requires that every organization needs information, not only business or government, but also the world of financial institutions. In accordance with this, the information technology has very important position in banking.  The purpose of this research is to analyze and to test empirically the influence of social factors, affect on intentions and its impact on financial behavior in utilizing internet banking technology as communication media. The method used in data collection is survey method by spreading the questionnaires. The research data obtained is based on the perception of students of Economics Faculty, University of Semarang on the use of internet banking technology implemented by Assistant Branch Bank of BNI Bank in University of Semarang environment as medium of communication between students and University of Semarang, with 96 respondents. The research method used validity test, reliability test, and classical assumption test, hypothesis test, multiple linear regression models with SPSS 23. Result of testing and analysis found that social factor and affects directly and indirectly did not affect the financial behavior of internet banking technology utilization implemented by Assistant Branch Bank of BNI Bank in University of Semarang environment as communication media of students with university, through the intention of internet banking technology usage by showing insignificant results.